The Influence of E-Service Quality and Trust through User Interest on LAPAK ASIK Usage Decisions - Ika Rakhma Kusuma Wardhani; Agustin Hari Prastyowati; Muhaimin Dimyati (Universitas Pendidikan Indonesia, 2025)
The Covid-19 pandemic spurred the transformation of digital-based public services, exemplified by the innovative Contactless Service (LAPAK ASIK) launched by BPJS Ketenagakerjaan to maintain service quality amidst physical interaction restrictions. Although the number of claims through LAPAK ASIK in BPJS Ketenagakerjaan KC Banyuwangi continues to increase, challenges persist concerning the quality of digital services, the level of trust, and the interest of some participants in using it. This study aims to analyze the influence of E-Service Quality and Trust on Usage Decisions, with Interest as a mediating variable. The research employed a quantitative method with multiple linear regression analysis based on questionnaire data collected from BPJS Ketenagakerjaan participants who are LAPAK ASIK users. The results indicate that E-Service Quality and Trust significantly influence Interest, which subsequently mediates their impact on Usage Decisions. The majority of respondents rated this service positively in terms of efficiency, fulfillment, security, and system reliability, thereby strengthening their interest and consistency in usage decisions. These findings support the Technology Acceptance Model (TAM), which emphasizes the role of service quality, ease of use, and trust in shaping behavioral intention and actual decisions. Practically, this research underscores that enhancing the quality of digital services and building participant trust are key to optimizing LAPAK ASIK at BPJS Ketenagakerjaan KC Banyuwangi.